(3bUjOI aj GdehGYXs
(3ChdgG (B:s
(3hHYO aGdPi CHOjg Edi LfGH eYOf GdUdGM hGdfLG hQjMGf GdJVhY hGdcJGHI s
(3BNQgG (B:s
(3hGdBd hGdUMH GdcQGe hebJVi HGdNjQ CKQg age GdPjf HMHge djVGA ddecQhH bHQg agPG BNQ eG CQOfGg hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdXGgQjI (B(9304) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs